Microbial diversity gradients in the geothermal mud volcano underlying the hypersaline Urania Basin - Lazar, Cassandre Sara; Schmidt, Frauke; Elvert, Marcus; Heuer, Verena B.; Hinrichs, Kai-Uwe; Teske, Andreas P. (Frontiers in Microbiology, 2022)
Mud volcanoes transport deep fluidized sediment and their microbial communities and thus provide a window into the deep biosphere. However, mud volcanoes are commonly sampled at the surface and not probed at greater depths, with the consequence that their internal geochemistry and microbiology remain hidden from view. Urania Basin, a hypersaline seafloor basin in the Mediterranean, harbors a mud volcano that erupts fluidized mud into the brine. The vertical mud pipe was amenable to shipboard Niskin bottle and multicorer sampling and provided an opportunity to investigate the downward sequence of bacterial and archaeal communities of the Urania Basin brine, fluid mud layers and consolidated subsurface sediments using 16S rRNA gene sequencing. These microbial communities show characteristic, habitat-related trends as they change throughout the sample series, from extremely halophilic bacteria (KB1) and archaea (Halodesulfoarchaeum spp.) in the brine, toward moderately halophilic and thermophilic endospore-forming bacteria and uncultured archaeal lineages in the mud fluid, and finally ending in aromatics-oxidizing bacteria, uncultured spore formers, and heterotrophic subsurface archaea (Thermoplasmatales, Bathyarchaeota, and Lokiarcheota) in the deep subsurface sediment at the bottom of the mud volcano. Since these bacterial and archaeal lineages are mostly anaerobic heterotrophic fermenters, the microbial ecosystem in the brine and fluidized mud functions as a layered fermenter for the degradation of sedimentary biomass and hydrocarbons. By spreading spore-forming, thermophilic Firmicutes during eruptions, the Urania Basin mud volcano likely functions as a source of endospores that occur widely in cold seafloor sediments.